Non-psychotic disorders in patients with arterial hypertension - Sarzhevskyi Сергій; Khomitskyi Микола (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the 12th Scientific-Practical Conference of Students and Young Scientists "Medical Psychology 12.0: Aspects of Clinical Practice". It is dedicated to formation of sanogenic thinking as the way of avoiding obsessive thoughts.